Low-Skilled Unemployment, Biased Technological Shocks and Job Competition - Olivier Pierrard; Henri R. Sneessens (Institute for the Study of Labor (IZA), 2003)
The unemployment rise in EU countries has been particularly strong for low-skilled workers. This observation has often been explained in terms of biased technical change and relative wage rigidities. More attention has been paid recently to an alternative mechanism, the crowding-out of low-skilled workers by over-qualified workers. The objective of this paper is both methodological and empirical. We construct a dynamic general equilibrium model with two types of jobs and two types of workers and with search unemployment. The model is calibrated and simulated to examine the interactions between the ?skill bias? and ?crowdingout? mechanisms. When such interactions are accounted for, the model reproduces quite well the observed unemployment changes.
Keywords: E24; J23; J21; 330; skill bias; equilibrium search unemployment; ladder effect; crowding out; over-education; Ungelernte Arbeitskräfte; Theorie der Arbeitslosigkeit; Arbeitsplatzsuchmodell; Qualifikation; Technischer Fortschritt; Überqualifikation; Allgemeines Gleichgewicht; Theorie; Belgien